KEMAMPUAN MENULIS TEKS PROSEDUR BAHASA BUGIS MENGGUNAKAN MEDIA GAMBAR BERSERI SISWA KELAS VII SMPN 1 PINRANG - Al-alaa, Anita; Daeng, Kembong; Asri, Aswati (Journal Studies in Indonesian Language and Literature, 2024)
The aim of this research is to describe the ability to write Bugis language procedural texts using series of picture media for class VII students at SMPN 1 Pinrang. This research is descriptive quantitative in nature and the technique used to collect data in this research is the written test technique. The results of the research show that the majority of students (78%) are in the incapable category in writing Bugis language procedural texts using serial image media. This is based on the distribution of grades which shows that only 22% of students scored between 75-100. This is proven by the students' scores from the four aspects of the assessment, namely objectives, steps and reaffirmation. The obstacles faced by students in writing Bugis language procedural texts include poor understanding of procedural texts, limitations in mastering Bugis language vocabulary, as well as difficulties in applying them. Bugis grammar even though explanations and examples have been given. Therefore, more intensive practice is needed in writing Bugis language procedure texts to improve students' understanding of these texts, enrich their Bugis language vocabulary, and improve their use of Bugis language grammar.